Attitude and its predictors towards Sexual and reproductive health service among Podoconiosis patients in Wolaita Zone, South Ethiopia : Attitude and its predictors towards Sexual and reproductive health service - Lera, Temesgen; Abebe, Amene; Wolka, Eskinder; Anjulo , Temesgen (Ethiopian Journal of Reproductive Health, 2025)
Background: Sexual and reproductive health (SRH) encompasses an individual’s overall well-being in relation to sexuality and the reproductive system. It extends beyond specific reproductive health concerns to include broader issues of sexual health. Despite the availability of SRH services in primary health care units, approximately 4.3 billion people globally lack access to essential services such as prenatal, postnatal, contraceptive, and abortion care. Attitudes toward SRH significantly influence service utilization and the effective management of sexual health concerns. This study aimed to assess attitudes and associated factors towards SRH services among podoconiosis patients in Wolaita Zone, South Ethiopia. Methods: A community-based cross-sectional study was conducted among 836 reproductive-aged podoconiosis patients. Bivariable and multivariable logistic regression analyses were performed. A Cronbach’s alpha reliability test was conducted, with a value above 0.7 considered acceptable. Variables with a p-value less than 0.25 in the bivariable analysis were included in the multivariable model. A p-value < 0.05 and 95% confidence interval (CI) were used to determine statistical significance. Results: The study found that 499 participants (59.7%) had a favorable attitude towards SRH services, while 337 (40.3%) had an unfavorable attitude. Factors significantly associated with favorable attitudes included being female (AOR = 1.64, 95% CI: 1.08–2.49), residing in urban areas (AOR = 8.85, 95% CI: 5.54–14.1), living with the disease for 1–5 years (AOR = 0.41, 95% CI: 0.2–0.82), not fearing stigma (AOR = 1.6, 95% CI: 1.1–2.34), family awareness of the disease’s cause (AOR = 2.16, 95% CI: 1.08–4.32), regular use of health services (AOR = 3.32, 95% CI: 2.04–5.44), previous use of SRH services (AOR = 10.0, 95% CI: 5.93–16.98), and being able to move from place to place (AOR = 2.75, 95% CI: 1.37–5.56). Conclusion: A favorable attitude toward SRH services was observed in 59.7% of podoconiosis patients. Significant predictors of favorable attitudes included gender, residence, duration of illness, perceived stigma, family awareness, health service utilization, prior SRH service use, and mobility. Efforts to improve SRH attitudes among podoconiosis patients should focus on expanding health education in rural areas and promoting male involvement in health-seeking behaviors. Key words: Attitude, Reproductive age, Sexual and reproductive health, Sexual and reproductive health services, Wolaita, Ethiopia